Impact of economic freedom on the growth rate: A panel data analysis - Mohammed Ershad Hussain; Mahfuzul Haque (Economies, 2016)
This study looks at some non-conventional determinants of economic growth, with the help of the newly developed economic freedom index datasets of the Heritage Foundation/Wall Street Journal(HF/WSJ), which is a cumulative index derived from several sub-indices (trade freedom index, financial freedom, labor freedom, business and fiscal freedom index). The cumulative economic freedom index show us how open and business friendly a country is. The sub-indices show us openness across different sector of the economy, for example, the financial sector or the trade sector etc. Traditional neo-classical economic theories have explained economic growth looking at the supply of labor, capital and state of technology, with little attention being paid to institutional factors. The study presents evidence based on two panel data-sets. The first set consists of 186 countries over the period 2013, 2014 and 2015 that show institutional factors play a crucial role in economic growth. A second data-set with data for 57 countries for the period 2004-2014 also show a positive impact on the index on the growth rate of per capita GDP.
Keywords: O11; O38; O43; 330; economic growth; freedom index; GDP; panel data